The Influence Of Brand Image And Lifestyle On Iphone Product Purchasing Decisions (Case Study at Ibox Bencoolen Mall Bengkulu City) - Mimi Kurnia Nengsi; Reza Mahendra (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of brand image and lifestyle on purchasing decisions for Iphone products (Case Study at Ibox Bencoolen Mall Bengkulu City. This type of research is a type of quantitative descriptive research, the object of this research is consumers of Ibox Bencoolen Mall Bengkulu City. The sampling method uses a technique non probability namely accidental sampling.The number of respondents in this study were 110 people.The data collection method used a questionnaire.The data analysis technique used the Multiple Linear Regression Analysis Test, and the Hypothesis Test, namely the t test and f test. The results of this study can be concluded that the variable Brand Image has a positive effect on Purchasing Decisions, Lifestyle has a positive effect on Purchase Decisions, and Brand Image and Lifestyle together have a significant effect on Purchase Decisions for Iphone Products at Ibox Bencoolen Mall Bengkulu City.